PENGENDALIAN PENYAKIT HAWAR DAUN PHYTOPHTHORA PADA BIBIT KAKAO (Theobroma cacao L.) DENGAN BEBERAPA TINGKAT PENGENCERAN Bacillus subtilis F. Cohn - Nurul Umamah; Gunawan Tabrani; Yunel Venita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This research aims to suppress the pathogenic attack of       Phytophthora palmivora Butler fungi on cocoa seedlings by using dilution levels of B. subtilis F. Cohn so that cocoa seedling growth become better. The research carried out in the Plant Disease laboratory and experimental gardens Faculty of Agriculture, University of Riau. Preparation of the inoculum until to the last observation done in December 2017 to June 2018. The study was conducted in a completely randomized experimental design consisting of five treatments and 4 replications. The treatments tested were B. subtilis bacterial dilution levels, is that without dilution, 10-10 dilution, 10-9 dilution, 10-8 dilution and 10-7 dilution. The data obtained in analyzed of variance and continued by the Duncan’s new multiple range test (DNMRT) at 5% level. The results showed that B. subtilis bacterial dilution affected to the initial symptoms appeared disease, the intensity of the disease attack, seedling height, stem diameter and number of leaves of cocoa seedlings. Bacterial dilution of B. subtilis 10-7 dilution is the better in controlling of Phytophthora leaf blight disease of cocoa seedlings so that better growth of cocoa seedlings. Keywords: Cocoa seedlings, B. subtilis dilution, P. palmivora leaf blight.